Android application of bluetooth ibeacon tracking system - Wang, Ye (2017)
Ibeacon is an advanced technology which based on the Bluetooth Low Energy. The ibeacon hardware can establish a short-range network which can be detected by smart phone embedded with bluetooth technology. With the ibecaon tracking system, customers in the retail shop can get the commodity information and order online without the assistance of sales assistants. The whole project is based on the Spring framework and android development platform, using Java language, abided by the Spring-Springmvc-Mybatis (SSM) design pattern, equipping with Mysql database. The system is mainly based on the hardware from Estimote company which can provide stable signal. The main function of the software is that the ibeacon can arouse the application of android system, by which it can interactive with the back-end. Keywords: Ibeacon; Android operation system; Spring; Springmvc; Mybatis; Mysql